Dietary Stevioside Supplementation Alleviates Lipopolysaccharide-Induced Intestinal Mucosal Damage through Anti-Inflammatory and Antioxidant Effects in Broiler Chickens - Jiang, Jingle (Antioxidants (Basel), 2019)
The study was conducted to investigate the effects of dietary stevioside (STE) supplementation on the lipopolysaccharide (LPS)-induced intestinal mucosal damage of broiler chickens. A total of 192 one-day-old male Ross 308 broiler chicks were randomly divided into four treatments: (1) basal diet (CON); (2) basal diet supplemented with 250 mg/kg stevioside (STE); (3) basal diet + LPS-challenge (LPS); (4) basal diet supplemented with 250 mg/kg stevioside + LPS-challenge (LPS + STE). LPS-challenged groups received an intraperitoneal injection of LPS at 17, 19 and 21 d, whereas the CON and STE groups received a saline injection. The results showed that dietary STE supplementation normalized LPS-induced changes in protein expression of p-NF-κB and p-IκBα, mRNA expression of inflammatory genes (TLR4, NF-κB, and IFN-γ), tight junction-related genes (CLDN2, OCLN, and ZO-1), and antioxidant genes (Nrf2 and HO-1). LPS-induced decreases in serum diamine oxidase (DAO) level, villus height-to-crypt depth ratio, apoptotic index, and protein expression of proliferating cell nuclear antigen (PCNA) were reversed with dietary STE supplementation. Additionally, STE supplementation ameliorated the redox damage by reducing malondialdehyde (MDA) content and increasing total antioxidant capacity (T-AOC) and antioxidant enzyme activity. In conclusion, dietary stevioside supplementation could alleviate LPS-induced intestinal mucosal damage through anti-inflammatory and antioxidant effects in broiler chickens.